Sozialarbeit für Fussballfans - das Münchner Projekt: Prävention mit Programm, Pleite mit der Politik, Praxis mit der Polizei - Weis, Kurt (Kriminologische Forschung in den 80er Jahren ; [3,2], 1988)
In October 1982, for the first time in Germany, a juvenile was killed in open battle between opposing football fan groups. In May 1985, in the Heysel Stadium in Brussels, Belgium, riots and fights between English and Italian supporters of their respective teams and mistakes by organizers and police resulted in 39 dead at the Europcan Football Cup Final. Both events resulted in an increasing political actionism among German authorities and an increase in police manpower controlling stadia and the pathways between the stadium, the city centers and the stations of railroads, subways and other local transportation. Fan violence has moved from the sportsfield to areas that are farther from the stadium and from sport. The sport clubs and the organizers have no interest and see no need to concem themselves with "their fans". Communities and youth authorities with their social workers also hang back. The author reports on his experience in the city of Munich where - on behalf of the city - he established an independent agency for social work and adventure pedagogy for problematic football fans. Since the beginning of the 1980s in some German cities, so-called fan projects were established, e.g. Bremen (1981), Hamburg (1983), Frankfurt, Bielefeld, Berlin (1984), Hannover (1985). Usually, in these cities, often under the guidance of scientists from the respective local universities, unemployed social pedagogists and social workers were employed for one or two years to work with these fan groups. However, sound social work with fans demands long duration and continuity in personnel. Such social work is difficult and highly problematic because those employed constitute a buffer between the fans and hooligans on one side, and the police on the other, and are accused by both sides of contact and loyalty to the other, "wrong" side. The Munich (where there are two famous football clubs with large supporting groups of dubious reputation) fan project attempted to solve most of these problems and to achieve a balance between the conflicting interests of the representatives of social policy and the policies of law and order. In 1987 the association "ACTION and LEISURE Inc." was founded under the chairmanship of the author. Among its nine members were the director of the youth authority, department heads from youth work and street work, and the competent section heads from the police department and the district attorneys office. The 1987 budget of the city of Munich allotted 450.000 German marks for the first year of our work. However, the financial and the political situation in Munich changed, the city council froze the funds and the fan project was politically killed. In its size and concept it was unique in Germany. lt died before it could really get to work. The FC Bayern München, Munich's top club in the national Football League, was not interested in supporting us. Instead, they are now employing army drafties in their free time to keep order in the Munich Olympia Stadium. Now, in 1988, the Bavarian police take up the battle against football rowdies in new green battle dresses and with new weapons.